Institutional Branding in Islamic Education: The Role of Strategic Brand Image in Stakeholder Perceptions - Badarwan Badarwan; Syamsuddin Syamsuddin; Pairin Pairin; Sumianti Sumianti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Research on educational branding has been predominantly situated in higher education contexts and tends to position brand image as an outcome rather than an integrated strategic process, while studies examining branding as an institutional practice in Islamic secondary education remain limited. This study aims to analyze how branding image strategies are constructed through brand positioning, brand identity, and brand personality, and their implications for prospective students’ enrollment interest. Employing a qualitative case study design at MAN 1 Kendari, data were collected through in-depth interviews, non-participant observations, and document analysis, and analyzed using thematic analysis to identify recurring patterns of meaning. The findings reveal that brand positioning is clearly established through the integration of academic excellence and religious values in institutional vision, programs, and instructional practices; brand identity is consistently constructed through the alignment of institutional symbols, flagship programs, religious culture, and the dissemination of student achievements via digital media; and brand personality is reflected in institutional characteristics such as religiosity, discipline, environmental responsibility, and achievement orientation. The integration of these elements enhances parental trust, shapes positive public perceptions, and contributes to the increasing enrollment interest of prospective students. This study contributes by conceptualizing brand image as an institutional practice grounded in operational quality and accountability rather than merely a promotional activity, while extending the application of brand equity and brand personality theories within the context of Islamic secondary education.